2021
DOI: 10.2196/26763
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physicians’ Recall Bias of Work Hours With a Mobile App: Interview and App-Recorded Data Comparison

Abstract: Background Previous studies have shown inconsistencies in the accuracy of self-reported work hours. However, accurate documentation of work hours is fundamental for the formation of labor policies. Strict work-hour policies decrease medical errors, improve patient safety, and promote physicians’ well-being. Objective The aim of this study was to estimate physicians’ recall bias of work hours with a mobile app, and to examine the association between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…95 In addition, studies have demonstrated effects of recall bias associated with distorted time perception resulting from long work hours and inconsistencies in the accuracy of self-reported work hours, with self-reported work hours for the week prior consistently 9 hours (SD = 8.6) lower than those that were automatically app-recorded (p < .001). 96 Improvements in duty hour compliance were seen with programmatic intervention in major domains including (1) improving the accuracy and transparency of work hour reporting, (2) facilitating more timely interventions, and (3) structural schedule changes that included transition to a night float model, providing additional time off for more junior residents, and redesigning the model of clinical coverage. 97 These types of issues should be considered in the structuring of duty hour oversight programs.…”
Section: Practice Management Issues and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 In addition, studies have demonstrated effects of recall bias associated with distorted time perception resulting from long work hours and inconsistencies in the accuracy of self-reported work hours, with self-reported work hours for the week prior consistently 9 hours (SD = 8.6) lower than those that were automatically app-recorded (p < .001). 96 Improvements in duty hour compliance were seen with programmatic intervention in major domains including (1) improving the accuracy and transparency of work hour reporting, (2) facilitating more timely interventions, and (3) structural schedule changes that included transition to a night float model, providing additional time off for more junior residents, and redesigning the model of clinical coverage. 97 These types of issues should be considered in the structuring of duty hour oversight programs.…”
Section: Practice Management Issues and Suggestionsmentioning
confidence: 99%
“…Reported deterrents to accurate duty hour reporting by residents has included fear of programmatic punitive measures, poor peer perception or judgment, desire to retain control of their surgical education, and frustration with the administrative burden following violations 95 . In addition, studies have demonstrated effects of recall bias associated with distorted time perception resulting from long work hours and inconsistencies in the accuracy of self‐reported work hours, with self‐reported work hours for the week prior consistently 9 hours (SD = 8.6) lower than those that were automatically app‐recorded ( p < .001) 96 . Improvements in duty hour compliance were seen with programmatic intervention in major domains including (1) improving the accuracy and transparency of work hour reporting, (2) facilitating more timely interventions, and (3) structural schedule changes that included transition to a night float model, providing additional time off for more junior residents, and redesigning the model of clinical coverage 97 .…”
Section: Practice Management Issues and Suggestionsmentioning
confidence: 99%
“…A study involving college students, for instance, reported that their average total time of weekly smartphone use was 20.11 ± 12.40 h based on self-reports but nearly 29.39 ± 14.45 h as recorded by mobile apps [ 14 ]. In another study, it was found that, when asked to recall the average weekly work hours within the past month, physicians reported working for an average of 60.24 h per week, despite their mobile apps recording 66.94 h per week [ 15 ]. Figure 1 illustrates that there was, on average, a 11.5–12.0% reduction in work hours reported by the subjects themselves.…”
Section: The Strengths Of Mobile Apps As Research Tools For Precision...mentioning
confidence: 99%
“…Several survey studies of physicians have revealed that self-reporting or recall bias affects findings, where inflation or deflation of their perceived performance exists. 11,12 What is needed are more objective measures of assessment to assess preparedness more accurately for independent practice.…”
Section: Introductionmentioning
confidence: 99%